Obtención de bioetanol del Jacinto de agua (eichhornia crassipe) proveniente del embalse Sixto Durán Ballén mediante proceso enzimático - Terán Guerrero, Johnny Efrain (2013)
The objective was to obtain bioethanol from Water Jacinto plant (Eicchornia crassipes), from the reservoir Sixto Duran Ballen. Plants were subjected to a pre physical treatment a characterization through Chemical analyzes, the samples were adequate for hydrolyzed with the microorganism (Trichoderma Arzzianun) in three concentrations (1.5 × 10 ³ m³, 3.4 × 10 ³ m³ and 4.5 × 10 ³ m³) to a same reaction time of 840 hours at room temperature, then followed the respective fermentation of the sample, which was inoculated in 0.001m ³ of water the sample hydrolyzed with 0.01 kg of microorganism (Saccharomyces cereviceae) for 360 hours. The plant subjected to previous studies presented suitable values for the experimentation giving alcohol solubility - benzene 11.24%, Lignin 19.13% and cellulose 40.24% we also made an analysis that determinate that the amount of dissolved oxygen DO ) is very low because of the topsoil causing a pH with a minimum value of alkalinity and average conductivity. It managed to get up to 16 G ° of alcohol starting from the Water Jacinto Plant through the enzymatic process.